High-activity catalyst for preparing 2-methylfuran through furfural hydrodeoxygenation and preparation method of high-activity catalyst

By supporting Ni and Mo bimetals on porous biochar, a high-active catalyst is prepared, which solves the problem of high cost and low efficiency of precious metal catalysts in the prior art, and achieves efficient catalytic and cost reduction of furfural hydrodeoxygenation reaction.

CN119633834AActive Publication Date: 2025-03-18LIAONING NORMAL UNIVERSITY
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411826086.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
2044-12-12

AI Technical Summary

Technical Problem

In the prior art, precious metal catalysts are costly and inefficient, making them difficult to apply on a large scale, and non-precious metal heterogeneous catalysts have poor catalytic effects in furfural hydrodeoxygenation reaction.

Method used

Ni and Mo bimetals are supported on porous biochar, with the chemical formula of aNi-bMoOx/C, a is the mass percentage of Ni and the support, b is the mass percentage of Mo and the support, and x is the number of O, and a highly active catalyst is obtained by ultrasonic impregnation and pretreatment.

Benefits of technology

The activity of furfural hydrodeoxygenation reaction and the selectivity of 2-methylfuran are significantly improved, the cost of the catalyst is reduced, and the preparation method is simple, and the catalytic hydrogenation product is specialized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633834A_ABST
    Figure CN119633834A_ABST
Patent Text Reader

Abstract

The invention discloses a high-activity catalyst for preparing 2-methylfuran through furfural hydrodeoxygenation and a preparation method thereof, Ni and Mo bimetals are loaded on porous biochar, the chemical formula is aNi-bMoOx / C, a is the mass percentage of Ni to a carrier, a is equal to 0.6-1%, b is the mass percentage of Mo to the carrier, b is equal to 0.12-0.2%, x is the number of O, x is equal to 2-3, and the molar ratio of nickel to molybdenum is (7-14): 1. The prepared catalyst can be used for preparing 2-methylfuran through a furfural direct-method hydrodeoxygenation reaction, the metal content is only 1.2% of that of a non-metal carrier at most, the cost of the catalyst is reduced, the hydrodeoxygenation reaction activity of furfural and the selectivity of 2-methylfuran are remarkably improved, and when the molar ratio of metal nickel to furfural is 1: 30 and the reaction condition is 200 DEG C, the yield of 2-methylfuran is increased. The reaction lasts for 4 hours at most, the conversion rate of the obtained furfural is 99.9% at most, and the selectivity of the 2-methyl furan is 92.5% at most.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of multiphase catalysis, and particularly relates to a high-activity catalyst for preparing 2-methylfuran by hydrogenating and deoxygenating furfural and a preparation method thereof. Background Art

[0002] As an important organic intermediate, furan compounds are widely used in the fields of dyes, medicines, fuel additives, etc. In the direct hydrodeoxygenation process with furfural as the substrate, the aldehyde carbonyl group in the furfural molecule is first adsorbed on the surface of the catalyst in an inclined adsorption configuration, and is converted into the intermediate furfuryl alcohol through the hydrogen activation of the catalyst, and then a molecule of water (H2O) is removed to achieve hydrogenolysis of the CO bond and finally converted into 2-methylfuran. In the past, in the furfural hydrodeoxygenation reaction system, precious metal-based catalysts have high activity. For example, Sakthivel Kumaravel et al. prepared a series of Ru catalysts with different Ru / Ni ratios by in situ hydrothermal synthesis. x / Ni y / SBA-16 catalyst, and applied it to the hydrogenolysis process of furfural hydrodeoxygenation to 2-methylfuran. The catalyst showed good catalytic performance under mild reaction conditions, achieving 100% conversion of furfural and 88% selectivity for 2-methylfuran (Materials Chemistry and Physics 316 (2024) 129083). However, due to the high cost of precious metal ruthenium, it is difficult to apply it on a large scale. For this reason, people are committed to developing more economically valuable non-precious metal heterogeneous catalysts.

[0003] Wang et al. used a wet impregnation method to develop a bimetallic Ni-Cu alloy catalyst loaded on a ZSM-5 zeolite catalyst and used it for furfural hydrodeoxygenation to produce 2-methylfuran. However, when the furfural conversion rate was 100%, the yield of 2-methylfuran could only reach 78.8% (Fuel 353 (2023) 129233).

[0004] The Chinese invention patent application with announcement number CN 112264032 B discloses a catalyst for catalyzing the hydrogenation and deoxygenation of furfural to prepare 2-methylfuran. The catalyst is composed of Ni, Mo and a ZrO2 carrier. The molar ratio of Ni, Mo and the ZrO2 carrier is 0.1-0.4:0.1-0.4:1. When the NiMo / ZrO2 catalyst and the reaction raw material furfural mass ratio are 0.1:1, the reaction temperature is 180°C, the reaction hydrogen pressure is 3MPa, and the furfural hydrogenation reaction is catalyzed for 6 hours, the molar yield of the crude 2-methylfuran product is 94%.

[0005] The Chinese invention patent with the announcement number CN 113304756 B discloses "a Ni-Mo bimetallic alloy catalyst and its preparation method and application", which is to embed a small amount of Ni atoms into the MoO2 lattice to form an alloy to prevent Ni from agglomerating during high-temperature calcination, and because Ni and Mo are fully in contact, electron transfer occurs during the high-temperature process, and the electron transfer direction is transferred from Mo to Ni, so that the electron density on the Ni surface is increased. The yield of 2-methylfuran is improved under the metal particle size effect and electronic effect. The synergistic effect of the bimetallic alloy between Ni and Mo affects the size and electronic structure of metal nanoparticles and thus improves the catalytic performance of furfural hydrodeoxygenation to prepare 2-methylfuran. The specific production method is to mix acetylacetone, nickel and acetylacetonate molybdenum by ball milling, add an organic solvent to continue ball milling, dry, calcine to obtain a composite oxide, crush it, place it in a tubular furnace and reduce it in a hydrogen atmosphere to obtain a bimetallic alloy catalyst for catalyzing furfural hydrodeoxygenation to prepare 2-methylfuran. 5g isopropanol and 0.3g furfural were used as raw materials, and 0.05g Ni-Mo bimetallic alloy catalyst was used for catalytic reaction at 190°C. The furfural conversion rate was 80.0% and the 2-methylfuran selectivity was 78.1%. The reaction was carried out at 200°C and 1.0MPa for 7 hours, the furfural conversion rate was 100%, and the 2-methylfuran selectivity was 92.2%.

[0006] It can be seen that the prior art has catalysts using metal Ni and Mo as active components, but due to different preparation methods and different product components, the prepared catalysts have different catalytic effects when applied to furfural hydrodeoxygenation to 2-methylfuran. However, the common problems are that the amount of metal used in the catalyst is large, the reaction time is long when applied to furfural hydrodeoxygenation to 2-methylfuran, and there are still problems such as high cost and low efficiency. Summary of the invention

[0007] The present invention aims to solve the above technical problems existing in the prior art and provides a high-activity catalyst for preparing 2-methylfuran by hydrogenating and deoxygenating furfural and a preparation method thereof.

[0008] The technical solution of the present invention is: a high-activity catalyst for preparing 2-methylfuran by hydrogenating and deoxygenating furfural, characterized in that: Ni and Mo bimetallic are loaded on porous biochar, the chemical formula is aNi-bMoOx / C, a is the mass percentage ratio of Ni to the carrier, a=0.6-1%, b is the mass percentage ratio of Mo to the carrier, b=0.15-0.2%, x is the number of O, x=2-3, and the molar ratio of the metal nickel to molybdenum is 7-14:1.

[0009] Preferably, the porous biochar is prepared by using cellulose, corn stalks or coffee grounds as a carbon source, adding a pore-forming agent, and roasting; the pore-forming agent is sodium bicarbonate, sodium carbonate, sodium acetate, potassium carbonate, potassium bicarbonate or potassium acetate, and the mass percentage of the pore-forming agent to the carbon source is 10-50%; the roasting temperature is 600-900°C, the roasting atmosphere is N2 gas, and the gas flow rate is 80-200ml / min.

[0010] Preferably, the carbon source is cellulose, the pore-forming agent is NaHCO3, and the carbonization temperature is 800°C.

[0011] Preferably, a=0.6%, b=0.15%, and the molar ratio of metal nickel to molybdenum is 7:1.

[0012] Preferably, a=0.8%, b=0.2%, and the molar ratio of metal nickel to molybdenum is 7:1.

[0013] Preferably, a=1%, b=0.12%, and the molar ratio of metal nickel to molybdenum is 14:1.

[0014] A method for preparing the above-mentioned high-activity catalyst for furfural hydrodeoxygenation to 2-methylfuran is carried out in accordance with the following steps:

[0015] Step 1. Weigh a certain amount of porous biochar and disperse it in deionized water by ultrasonic to prepare solution A;

[0016] Step 2. Dissolve nickel salt and molybdenum salt in deionized water to prepare solution B with a metal concentration of 0.1 mol / L, slowly add solution B to solution A, and let stand at room temperature for 24 hours;

[0017] Step 3. Stir and evaporate to dryness and pre-treat at 500°C, 5% vol H2 or N2 mixed gas for 3 hours.

[0018] Preferably, the nickel salt is nickel nitrate, nickel chloride or nickel acetate, and the molybdenum salt is sodium molybdate or ammonium molybdate.

[0019] The aNi-bMoOx / C catalyst prepared by the present invention can be used for the hydrogenation and deoxygenation reaction of furfural to prepare 2-methylfuran. The metal content is only 1.2% of the non-metallic carrier (porous biochar) at most, which not only reduces the cost of the catalyst, but also significantly improves the hydrogenation and deoxygenation reaction activity of furfural and the selectivity of 2-methylfuran. When the molar ratio of metal nickel to furfural is 1:30, the reaction condition is 200°C, and the reaction time is up to 4 hours, the furfural conversion rate is as high as 99.9%, and the 2-methylfuran selectivity is as high as 92.5%. The catalyst has the advantages of simple preparation method, low material cost, good catalytic activity, high specificity of catalytic hydrogenation products, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is the XRD diffraction pattern of the catalysts of Example 2 and Comparative Examples 3, 5 and 9 of the present invention.

[0021] Figure 2 It is the XRD diffraction pattern of Example 2 of the present invention and Comparative Examples 6, 7 and 8. DETAILED DESCRIPTION

[0022] Embodiment 1:

[0023] The high-activity catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural of the present invention is carried out in the following steps:

[0024] Step 1. Weigh a certain amount of porous biochar and disperse it in deionized water by ultrasonic to prepare solution A;

[0025] The preparation method of the porous biochar is as follows: 3 grams of cellulose and 1.5 grams of NaHCO3 are fully physically mixed and ground in a mortar, and then transferred to a quartz boat, heated to 800°C at 10°C / min in a tube furnace under an 80mL / min N2 atmosphere, high-temperature carbonized for 60 minutes, cooled to room temperature, ground into powder, dispersed in 200mL of deionized water, magnetically stirred at room temperature for 12 hours, washed with deionized water several times until the pH of the filtrate is ≈7, and the obtained solid is dried at 70°C overnight to obtain porous biochar.

[0026] Step 2. Dissolve nickel nitrate and sodium molybdate dihydrate in deionized water at a molar ratio of nickel to molybdenum of 7:1 to prepare a solution B with a metal concentration of 0.1 mol / L. Slowly add solution B to solution A and allow to stand at room temperature for 24 hours.

[0027] Step 3. Stir and evaporate to dryness and pretreat at 500°C, 5% vol H2 atmosphere for 3 hours to obtain a catalyst with a Ni to carrier mass percentage of 0.6% and a Mo to carrier mass percentage of 0.15%, named 0.6Ni-0.15MoOx / C-500.

[0028] Embodiment 2:

[0029] The preparation method is different from that of Example 1 in that the mass percentage of Ni to the carrier is 0.8%, and the mass percentage of Mo to the carrier is 0.2%. The rest is the same as Example 1, and the obtained catalyst is named 0.8Ni-0.2MoOx / C-500.

[0030] Embodiment 3:

[0031] The preparation method is different from that of Example 1 in that the molar ratio of nickel to molybdenum is 14:1, the mass percentage of Ni to carrier is 1%, and the mass percentage of Mo to carrier is 0.12%. The rest is the same as Example 1, and the obtained catalyst is named 1Ni-0.12MoOx / C-500.

[0032] Comparative Example 1:

[0033] The preparation process is the same as that of Example 1, except that only nickel nitrate solution is used as the metal salt, and the mass percentage of the metal salt to the carrier is 0.8%. The obtained catalyst is named 0.8Ni / C-500.

[0034] Comparative Example 2:

[0035] The preparation process is the same as that of Example 1, except that only sodium molybdate solution is used as the metal salt, and the mass percentage of the metal salt to the carrier is 0.8%. The obtained catalyst is named 0.8MoOx / C-500.

[0036] Comparative Example 3:

[0037] The preparation method is different from that of Example 1 in that the mass percentage of Ni to the carrier is 1%, and the mass percentage of Mo to the carrier is 0.25%. The rest is the same as Example 1, and the obtained catalyst is named 1Ni-0.25MoOx / C-500.

[0038] Comparative Example 4:

[0039] The preparation method is different from that of Example 1 in that the mass percentage of Ni to the carrier is 1%, and the mass percentage of Mo to the carrier is 0.5%. The rest is the same as Example 1, and the obtained catalyst is named 1Ni-0.5MoOx / C-500.

[0040] Comparative Example 5:

[0041] The preparation method is different from that of Example 1 in that the mass percentage of Ni to the carrier is 5%, and the mass percentage of Mo to the carrier is 1%. The rest is the same as Example 1, and the obtained catalyst is named 5Ni-1MoOx / C-500.

[0042] Comparative Example 6:

[0043] The preparation method is different from that of Example 2 in that the catalyst is stirred and evaporated to dryness and pretreated in a 5% vol H2 atmosphere at 400°C for 3 hours. The rest is the same as that of Example 1. The obtained catalyst is named 0.8Ni-0.2MoOx / C-400.

[0044] Comparative Example 7:

[0045] The preparation method is different from that of Example 2 in that the catalyst is evaporated to dryness by stirring and pretreated at 600°C in a 5% vol H2 atmosphere for 3 hours. The rest is the same as that of Example 1. The obtained catalyst is named 0.8Ni-0.2MoOx / C-600.

[0046] Comparative Example 8:

[0047] The preparation method is different from that of Example 2 except that the catalyst is evaporated to dryness with stirring and pretreated at 700°C, 5% vol H2 atmosphere for 3 hours. The other preparation methods are the same as those of Example 1. The obtained catalyst is named 0.8Ni-0.2MoOx / C-700.

[0048] Comparative Example 9:

[0049] The preparation method is different from that of Example 1 in that the mass percentage of Ni to the carrier is 2%, and the mass percentage of Mo to the carrier is 0.5%. The rest is the same as Example 1, and the obtained catalyst is named 2Ni-0.5MoOx / C-500.

[0050] The XRD diffraction patterns of the catalysts of Example 2 and Comparative Examples 3, 5, and 9 are as follows: Figure 1 The characteristic diffraction peaks at about 43.8° and 51.2° are attributed to the crystal phase diffraction peaks of metallic nickel. The metallic nickel diffraction peaks of the catalyst in Example 2 and the catalysts in Comparative Examples 3 and 9 are relatively weak, indicating that the metal is highly dispersed on the surface of the porous carbon carrier.

[0051] The XRD diffraction patterns of Example 2 of the present invention and Comparative Examples 6-8 are as follows: Figure 2 As shown. Figure 2 It can be seen that the pretreatment temperature has an effect on the intensity of the crystal phase diffraction peak of metallic nickel. When the catalyst is pretreated above 500°C, the crystal phase diffraction peak of Ni begins to strengthen, which indicates that the pretreatment temperature of 500°C can better maintain the high dispersion of metallic Ni.

[0052] Catalytic performance evaluation experiment:

[0053] Experimental method: 1mmol furfural, 10ml isopropanol and catalyst were added to a high pressure reactor. The amount of catalyst was adjusted according to the molar ratio n Ni :n FAL =1:30 for quantitative analysis. After sealing, nitrogen was purged 3 times. After hydrogen replacement, the hydrogen pressure was maintained at 1Mpa, the stirring speed was 500r / min, the temperature was raised to 180℃ or 200℃, and the reaction time was 120min or 240min. After the reaction was completed, the reactor was cooled to room temperature, the supernatant was taken, and qualitative and quantitative analysis was performed by gas chromatography.

[0054] Experimental results: The activity evaluation graphs of the catalysts of Examples 1, 2, 3 of the present invention and Comparative Examples 1-9 are shown in Table 1. In Table 1, FAL is furfural, 2-MF is 2-methylfuran, FOL is furfuryl alcohol, THFOL is tetrahydrofurfuryl alcohol, and Other is other byproducts.

[0055] Table 1

[0056]

[0057] From Table 1 we can see that:

[0058] 1. Under the same reaction conditions, both Comparative Example 1 (0.8Ni / C-500) and Comparative Example 2 (0.8MoOx / C-500) showed relatively low catalytic performance, while the catalytic performance of the catalysts doped with a small amount of Ni and Mo (<0.2wt%) in Comparative Examples 3-7 was improved, indicating that there was a strong interaction between Ni and Mo. In addition, with the increase of the metal loading (Ni+Mo) in the catalyst, the conversion rate of furfural and the selectivity of 2-methylfuran gradually decreased, and only Examples 1-3 of the present invention showed excellent catalytic activity, among which the 0.6Ni-0.15MoOx / C-500 catalyst had the best hydrodeoxygenation catalytic activity, with a furfural conversion rate of 99.9% and a 2-MF selectivity of 92.5%.

[0059] 2. The catalytic performance of catalysts with different Ni and Mo molar ratios is different. When the metal molar ratio of Ni and Mo is 7:1 or 14:1, the hydrodeoxygenation performance of FAL on the catalyst is better. After four hours of reaction, the furfural conversion rate can reach 99.9%, and the highest 2-methylfuran selectivity is 92.5%; when the metal molar ratio of Ni and Mo is 3:1, the performance of the catalyst is poor, the furfural conversion rate is only 24.0%, the 2-methylfuran selectivity is 39.4%, and more by-products are generated.

[0060] 3. The catalytic activity of the 0.6Ni-0.15MoOx / C-500 catalyst in Example 1 was evaluated at 180°C and 200°C. When the other reaction conditions were the same, the furfural conversion rate was 99.9% and the 2-methylfuran selectivity was 89.7% when the reaction was carried out at 180°C for 2 hours; the furfural conversion rate was 99.9% and the 2-methylfuran selectivity was 92.5% when the reaction was carried out at 200°C for 4 hours.

[0061] 4. The change of pretreatment temperature under H2 / N2 atmosphere has a significant effect on the catalytic performance of the catalyst. When the pretreatment temperature is in the range of 400-700°C, the furfural conversion rate and 2-MF selectivity of the four catalysts in Example 2 and Comparative Examples 6-8 first increase and then decrease. Among them, the furfural conversion rate on the 0.8Ni-0.2MoOx / C-500 catalyst is 99.9%, and the 2-methylfuran selectivity is 88%, indicating that 500°C is the optimal pretreatment temperature for the catalyst of the present invention.

[0062] Experimental results show that the catalyst prepared according to the metal to porous biochar mass ratio, Ni to Mo molar ratio and specific pretreatment temperature specified in the present invention has high catalytic activity for the furfural hydrodeoxygenation reaction to prepare 2-methylfuran.

Claims

1. A highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural, characterized in that: The porous biochar is loaded with Ni and Mo bimetallics, with a chemical formula of aNi-bMoOx / C, where a is the mass percentage of Ni to the carrier, a=0.6-1%, b is the mass percentage of Mo to the carrier, b=0.12-0.2%, x is the number of O, x=2-3, and the molar ratio of the metal nickel to molybdenum is 7-14:

1.

2. The highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 1, characterized in that: The porous biochar is prepared by taking cellulose, corn stalks or coffee grounds as carbon sources, adding a pore-forming agent, and roasting; the pore-forming agent is sodium bicarbonate, sodium carbonate, sodium acetate, potassium carbonate, potassium bicarbonate or potassium acetate, and the mass percentage of the pore-forming agent to the carbon source is 10-50%; the roasting temperature is 600-900°C, the roasting atmosphere is N2 gas, and the gas flow rate is 80-200ml / min.

3. The highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 2, characterized in that: The carbon source is cellulose, the pore-forming agent is NaHCO3, and the carbonization temperature is 800°C.

4. The highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 2, characterized in that: The a=0.6%, b=0.15%, and the molar ratio of metal nickel to molybdenum is 7:

1.

5. The highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 2, characterized in that: The a=0.8%, b=0.2%, and the molar ratio of metal nickel to molybdenum is 7:

1.

6. The high-activity catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 2, characterized in that: The a=1%, b=0.12%, and the molar ratio of metal nickel to molybdenum is 14:

1.

7. The method for preparing a highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 1 or 2, characterized in that Follow the steps below: Step 1. Weigh a certain amount of porous biochar and disperse it in deionized water by ultrasonic to prepare solution A; Step 2. Dissolve nickel salt and molybdenum salt in deionized water to prepare solution B with a metal concentration of 0.1 mol / L, slowly add solution B to solution A, and let stand at room temperature for 24 hours; Step 3. Stir and evaporate to dryness and pretreat at 500°C in 5% vol H2 / N2 mixed gas for 3 hours.

8. The method for preparing a highly active catalyst for preparing 2-methylfuran by hydrodeoxygenation of furfural according to claim 7, characterized in that: The nickel salt is nickel nitrate, nickel chloride or nickel acetate, and the molybdenum salt is sodium molybdate or ammonium molybdate.

Citation Information

Patent Citations

  • A catalyst for the catalytic hydrogenation and deoxygenation of furfural to prepare 2-methylfuran

    CN112264032B

  • A Ni-Mo bimetallic alloy catalyst, its preparation method and application

    CN113304756B

  • Preparation method and application of reduced NiMo bifunctional catalyst

    CN111298799A

  • Preparation method of hydrodesulfurization catalyst

    CN111298801A

  • Catalyst for catalyzing furfural hydrodeoxygenation to prepare 2-methylfuran

    CN112264032A